KARI's Technology and Information Response Initiative - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
In June 2000, KARI launched the Agricultural Technology and Information Response Initiative (ATIRI), an experimental programme to elicit the farmers´ demands for appropriate agricultural technologies and innovations, and to improve their disseminati